Administrative Contract as a Legal Form of Public Administration: Updating Doctrinal Approaches (Law and Safety, 2019)
The analysis of the features of administrative contracts, formed by the theory of administrative law, has been made for the purpose of their compliance with the current legislation. The perspectives of improving both the doctrinal understanding and the normative construction of the concept of administrative contracts have been clarified. It has been stated that administrative contracts are only one of the possible contractual forms of regulating the relations of public administration. Contractual regulators can be both formalized in the form of administrative contracts or unformalized, when the agreement between the authorities is fixed at the level of legal acts or when laws provide the possibility of reaching a consensus in vertical and horizontal administrative legal relations. The author has established the correlation between administrative contracts and other types of legal forms, including with administrative acts, the common legal acts. The perspectives for improving the list of types of administrative contracts have been stated. In particular, the author has substantiated that the list of cases of concluding administrative contracts, under the Code of Administrative Judiciary of Ukraine, focuses solely on the determination of the substantive jurisdiction of administrative courts and is only a basis for forming the scope of the concept of “administrative contracts”, which is much more wider than the legal definition.It has been pointed out that some of the statements made in the most recent writings on administrative contracts are falsified, including that administrative contracts and administrative acts are comparable incompatible concepts, and the initiative in concluding administrative contracts can come from an authorized subject, as well as from legal entities and individuals.The author has concluded about the significant influence of the normative construction of the concept of administrative contracts on its doctrinal understanding and the need to update the established ideas about its function as a legal form of public administration, which directs the study of those types of economic contracts, which in their essence are administrative contracts.
Keywords: legal form; public administration; administrative contract; contractual form